Suspension of the employment contract and reduction of working time due to economic, technical, organizational or productive grounds regulated by article 47 of the Statute of Workers (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This study analyses the procedure of suspension and reduction of working time due to economic, technical, organizational or productive grounds regulated by article47 of the Statute of Workers, after the important modifications introduced by the Labour Reform 2012 (including the rules of the Royal Decree 1483/2012, of 29 October). The study is distributed in several sections including the review of the grounds in which these procedures are based –grounds that will be necessarily of temporary nature–, the procedure of negotiation –once eliminated the administrativeauthorization of the labour authority– and the means to claim before the courts the decisions finally taken by the employer.
Keywords: Reducción; Jornada; Suspensión; Procedimiento; Colectivo